Trauma-informed sentencing in South Australian courts. Issue 4 (December 2022) - McLachlan, Katherine J
Recently the concepts of 'compassionate courts', 'humane justice', 'kindness in court', and trauma-informed practice have emerged in legal theory and practice in the US, England, Scotland and Australia. This article uses a trauma-informed practice framework to examine how South Australian superior court judges acknowledge defendant trauma in sentencing. Trauma-informed sentencing practice requires that judges realise the presence of trauma, recognise its relevance, respond in a way that is informed by trauma and act to resist re-traumatisation. By using this '4Rs' framework to analyse sentencing remarks of 448 defendants published in 2019, the presence of trauma-informed practice was explored. Analysis indicated that judges realised trauma was present in the lives of many defendants, particularly women and Aboriginal peoples, but did not always overtly recognise a link between trauma and criminal behaviour and were unlikely to refer to a defendant's trauma history or use trauma-informed principles of practice in their sentencing response. Research findings were presented to judicial officers at a Judicial Development Day in 2021. The article reflects on those discussions as well as the primary research, when making recommendations for future sentencing practice primary for the judiciary, but also for legislators and legal practitioners.